Comparative effect of sunflower seed oil (helianthus annus l.) On the characteristics and quality of liquid soap formulations - lestari, Tri Puji; Evi Kurniawati; Ida Kristianingsih; Asih Imulda Hari Purwani (Sean Institute, 2024)
Sunflower seed oil contains linoleic acid which can moisturize the skin and has high antioxidant activity so it can inhibit free radicals which damage skin cells. The liquid soap made in this research uses VCO (Pure (Virgin Coconut Oil) which contains high levels of lauric acid as a raw material for making soap because it is able to provide very soft foam for soap products. The aim of this research is to determine the characteristics of liquid soap preparations from oil. Sunflower seeds (Helianthus annuus L.) with different concentrations of sunflower seed oil of 5% and 10% as the active substance. Physical quality tests were also carried out including organoleptic tests, homogeneity tests, pH tests, free alkali tests, specific gravity tests, stability, and foam height tests. Based on the results of physical quality tests that have been carried out on the sunflower seed oil liquid soap formulation, it has met the requirements of the organoleptic test, homogeneity test, pH test, specific gravity test, and foam height test. Based on the analysis test results, it shows that there is no there is significant difference in the physical quality tests between formula 1 and formula 2